The Difference of Trapped Rats Number between Uncombinated and Combinated Bait - Khoirunnisa, Rizka; Siwiendrayanti, Arum (Unnes Journal of Public Health)
Abstract Rats become important pests in human life. Control of rats using live traps can only catch the rats in the first time the trap is set, for the following days no rats enter the trap. The purpose of this study was to determine whether there were differences in the number of rats trapped between the method of combined feeding with non-combined feeding. This type of research used in this study was quasi-experimental (quasi experiment) with a posttest only nonequivalent control group design. Each house has 5 traps installed with 6 repetitions. One trap was installed by combining bait types and four other traps were installed without combining bait types. The instruments used were house screening sheets, traps, and observation sheets. The data obtained were tested with the Mann-Whitney test. The results of the study showed that the number of rats trapped between combined feeding with anchovies (p = 0.048), combined feeding with rice (p = 0.272), fed combination with tofu (p = 0.443) and combined feeding with grilled coconut (p = 0.443). The most common trapping of the rats is the feeding of anchovies, while the most consistent trapping of mice is the combination of feeding and feeding of anchovies.